1997
DOI: 10.1021/jo960710g
|View full text |Cite
|
Sign up to set email alerts
|

Probing for Electronic and Steric Effects in the Peracid Oxidation of Thianthrene 5-Oxide

Abstract: A systematic examination of the electronic and steric effects in the peracid oxidation of thianthrene 5-oxide (SSO) was undertaken and has revealed valuable information on the oxidative reactivity of the SSO mechanistic probe toward peroxidic oxidants. Thus, no significant steric effect was found on the bisulfoxide (SOSO)/sulfone (SSO(2)) product ratio for aliphatic peracids with varying size of alkyl groups [R = Me, Et, i-Pr, t-Bu, (n-Bu)(Et)CHCH(2)]. However, a significant electronic effect was observed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 20 publications
4
30
0
Order By: Relevance
“…Our balance of products, Th and ThO is in accord with this requirement. The oxidation mechanism of ThO by dimethyldioxirane 19 or peracid 20 is analogous to the present results. They have shown that the nucleophilic oxidant such as peracid and dimethyldioxirane led exclusively to oxidation of the sulfoxide site than nucleophilic sulfide site to the SSO 2 .…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Our balance of products, Th and ThO is in accord with this requirement. The oxidation mechanism of ThO by dimethyldioxirane 19 or peracid 20 is analogous to the present results. They have shown that the nucleophilic oxidant such as peracid and dimethyldioxirane led exclusively to oxidation of the sulfoxide site than nucleophilic sulfide site to the SSO 2 .…”
supporting
confidence: 90%
“…Concentration factors for all products were determined with authentic materials. Thianthrene-5,10-dioxide (SOSO), 20 and thianthrene 5,5-dioxide (SSO 2 ), 20 were prepared as described in the literature. The samples were submitted to GC and GC/MS analyses.…”
Section: Methodsmentioning
confidence: 99%
“…[6,7] Such epoxidation reactions have been extensively investigated by computational methods. [8Ϫ14] Recently we reported [15] that calculated activation barriers in the gas phase correlate in a linear fashion with the energy gap between the olefin HOMO π(CϪC) and the LUMO σ*(OϪO) of the epoxidizing peroxo group, as found previously also for epoxidation by transition metal peroxo complexes.…”
Section: Introductionmentioning
confidence: 99%
“…They proved that the formation of sulfone 4 cannot take place via the DMD oxidation of the sulfinyl oxygen of thianthrene 5-oxide (3) (Scheme 3). Later, Adam et al [32][33][34] reinvestigated the dioxirane oxidation of the thianthrene 5-oxide (3). The careful analysis of all the reaction products unequivocally proved that both dimethyldioxirane (1) and methyl(trifluoromethyl)dioxirane (2) are strongly electrophilic oxidants.…”
Section: Methodsmentioning
confidence: 99%